Evaluating the Randomness of the RNG in a Commercial Smart Card - Ribeiro, Wellinton Costa; Silva, Marcus Tadeu Pinheiro (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2017: Anais do XVII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2017)
This paper brings results concerning the quality evaluation for the pseudo-random number generator (PRNG) in a commercial smart card. The RNG is a fundamental part for the cryptography carried out in several applications. We have acquired a huge quantity of random numbers from three samples of a commercial smart card. These data were evaluated using the statistical computation package developed by National Institute of Standards and Technology. In order to be used as gold benchmark and to validate our methodology, we have also tested the true random number generator (TRNG) included in a commercial integrated circuit. Our results show that the card PRNG owns quality too inferior than the TRNG. Due to card vendor confidentiality policy is not possible state the tested PRNG is base for the device cryptography. However, if this occurs, results lead us to conclude the tested PRNG is not adequate to provide the required security in the systems that adopt the evaluated smart card.